Hybrid Tumor of the Parotid Gland: A Case Report and Review of the Literature. (9th February 2015) - Sabri, Alain; Bawab, Ibrahim; Khalifeh, Ibrahim; Alam, Elie
Abstract : The parotid gland is the most common location of benign neoplasms affecting major salivary glands. Hybrid tumors are very rare tumor entities which are composed of two different tumor types, each of which conforms to an exactly defined tumor category. The tumor entities of a hybrid tumor are not separated but have an identical origin within the same topographical area. This report describes a 51-year-old male with three neoplasms occurring within a single parotid gland tumor. The clinical, radiological, and histologic features are described in addition to a review of the literature.